COST-EFFECTIVENESS EVALUATION OF PREHOSPITAL THROMBOLYSIS WITH TENECTEPLASE - V. V. Omel'yanovskiy (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2016)
Aim. To evaluate clinical and cost effectiveness of different reperfusion strategies in myocardial infarction with ST segment elevation (STEMI), including pre-hospital thrombolysis with tenecteplase.  Material and methods. Methods of cost-effectiveness analysis and economic modeling were used to calculate the costs of reperfusion in STEMI, expected number of life gains, the cost of life gains depending on reperfusion strategy (no reperfusion, percutaneous coronary intervention (PCI), prehospital thrombolysis, hospital thrombolysis).  Results. In accordance to analysis results and from economic point of view, the most effective strategy is primary PCI in patients within "therapeutic window" and pre-hospital thrombolysis in the remaining patients with STEMI. More complex strategy of patients flow control with patient division into groups of primary PCI, pre-hospital thrombolysis and hospital thrombolysis lead to decrease in reperfusion costs efficacy.  Conclusion. The reperfusion model with primary PCI in the first 120 minutes after STEMI symptoms onset, and pre-hospital thrombolysis with bolus thrombolytic administration, when PCI is not possible in this period, is the most effective economically and in respect on mortality reduction in patients with STEMI.